A study of secondary school students' perceptions towards reader's response in the study of literature texts / Nik Mohd Afiq Nik Luqman - Nik Luqman, Nik Mohd Afiq (2011)
This study investigated secondary school students' perceptions towards reader's response in the study of literature texts. It also examined students' opinions of the current methods of teaching literature. The subjects of this study involved 42 Form 4 students from SMK TTDI Java Shah Alam. The study employed one system of collecting data, a Questionnaire. The findings in this study indicate that students feel that readers' response is important in the study of literature texts. The analysis also indicates that the use of readers' response does have a certain impact on the students' language performance. These findings suggest that in order for readers1 response to be implemented, students and teachers should put in extra effort to make it happen. The most significant finding reveals that teachers must question students so that they can think critically and relate the texts to their personal life and keep giving their opinions so that they can develop a deeper understanding of the texts.